Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 4.(x-3)=72-13
=> 4(x - 3) = 49 - 1
=> 4(x - 3) = 48
=> x - 3 = 12
=> x = 15
b, 5x+x=150:2+3
=> 6x + = 75 + 3
=> 6x = 78
=> x = 13
a) 4(x-3)=72-13
<=> 4(x-3)=49-1
<=> 4(x-3)=48
<=> x-3=12
<=> x=15
Vậy x=15
b) 5x+x=150:2+3
<=> 6x=75+3
<=> 6x=78
<=> x=13
Vậy x=13
\(a)\left(3\frac{1}{2}-x\right).1\frac{1}{4}=\frac{15}{6}\)
\(\left(\frac{7}{2}-x\right).\frac{5}{4}=\frac{15}{6}\)
\(\frac{7}{2}-x=\frac{15}{6}:\frac{5}{4}\)
\(\frac{7}{2}-x=2\)
\(x=\frac{7}{2}-2\)
\(\Rightarrow x=\frac{3}{2}\)
Bài 1: Tìm X
a, 32.(x+4)-52=5.22
⇒ 32 .(x+4)-25 =20
⇒9 . (x+4) = 20+25=45
⇒ x+4 = 45: 9 = 5
⇒ x = 5-4 = 1
Vậy x = 1
b,5x+x=39-311:39
⇒ 6x = 39 - 32 =39-9=30
⇒ x = 30 : 6 = 5
Vậy x = 5
c(3x -24 ).73 =2.74
⇒ 3x -24 = 2 . 74 : 73
⇒ 3x - 16 = 2 . 7 = 14
⇒ 3x = 14+16=30
Mà 33=27 , 34 = 81
⇒ x = ∅
Bài 2
a, 66.25+5.66+66.14+33.66
= 66 . ( 25+5+14+33 )
= 66 . 77 = 5082
a, 100 - 7 ( x - 5 ) = 31 + 33
100 - 7 ( x - 5 ) = 31 + 27
100 - 7 ( x - 5 ) = 58
7 ( x - 5 ) = 100 - 58
7 ( x - 5 ) = 42
x - 5 = 42 : 7
x - 5 = 6
=> x = 6 +5
=> x = 11
Vậy x = 11
b, 12 ( x - 1 ) : 3 = 43 + 23
12 ( x - 1 ) : 3 = 64 + 8
12 ( x - 1 ) : 3 = 72
12 ( x - 1 ) = 72 . 3
12 ( x - 1 ) = 216
x - 1 = 216 : 12
x - 1 = 18
=> x = 18 + 1
=> x = 19
Vậy x = 19
c, 24 + 5x = 75 : 73
24 + 5x = 72
24 + 5x = 49
5x = 49 - 24
5x = 25
=> x = 25 : 5
=> x = 5
Vậy x = 5
d, 5x - 206 = 24 . 4
5x - 206 = 16 . 4
5x - 206 = 64
5x = 64 + 206
5x = 270
=> x = 270 : 5
=> x = 54
Vậy x = 54
e, 125 = x3
53 = x3
=> x = 5
Vậy x = 5
g, 64 = x2
82 = x2
=> x = 8
Vậy x = 8
a.\(\Rightarrow\left(\frac{3}{5}+x\right):\frac{2}{7}=\frac{3}{35}-\frac{2}{7}\)
\(\Rightarrow\left(\frac{3}{5}+x\right):\frac{2}{7}=-\frac{1}{5}\)
\(\Rightarrow\frac{3}{5}+x=-\frac{1}{5}.\frac{2}{7}\)
\(\Rightarrow\frac{3}{5}+x=-\frac{2}{35}\)
\(\Rightarrow x=-\frac{2}{35}-\frac{3}{5}\)
Vậy \(x=-\frac{23}{35}\).
b. => 5x-1=0 hoặc 2x-1/3=0
=> 5x=1 hoặc 2x=1/3
=> x=1/5 hoặc x=1/6
c. \(\Rightarrow\frac{1}{7}:x=\frac{3}{14}-\frac{3}{7}\)
\(\Rightarrow\frac{1}{7}:x=-\frac{3}{14}\)
\(\Rightarrow x=\frac{1}{7}:\left(-\frac{3}{14}\right)\)
Vậy \(x=\frac{-2}{3}\).
\(a,4\left(x-3\right)=7^2-1^3\)
\(4\left(x-3\right)=49-1\)
\(4\left(x-3\right)=48\)
\(\Rightarrow x-3=48:4\)
\(x-3=24\)
\(\Rightarrow x=27\)
\(5x+x=\frac{150}{2}-3\)
\(6x=75-3\)
\(6x=72\)
\(\Rightarrow x=12\)
a, 4( x - 3) = 72 - 13
<=> 4x - 12 = 49 - 1
<=> 4x = 49 - 1 +12
<=> x = 15
Vậy....
b, 5x + x = \(\frac{150}{2}\)+ 3
<=> 5x + x = 75 + 3
<=> 6x = 78
<=> x = 13
Vậy......